Effect of Nigella sativa L. Seed on the Kidney of Monosodium Glutamate Challenged Rats - Abd-Elkareem, Mahmoud; Soliman, Mahmoud; Abd El-Rahman, Mokhless A. M.; Abou Khalil, Nasser S. (Frontiers in Pharmacology, 2022)
Monosodium glutamate (MSG) consumption is responsible for a wide spectrum of health hazards including nephrotoxicity. The search for phytochemical strategies having broad safety profile to counter MSG toxicity is worthwhile. Nigella sativa L. seed (NSS) is very promising in this regard owing to its antioxidant and cytoprotective nature. Therefore, we attempted to investigate the potential protective effect of NSS on MSG-induced renal toxicity in rats. To accomplish this objective, fifteen adult Wistar albino rats were randomly and equally divided into three groups for 21 days: the control group received no treatment, MSG group supplemented with MSG at a dose of 30 g/kg feed, and MSG+NSS group supplemented with MSG at the same previous dose in conjugation with NSS at a dose of 30 g/kg feed. MSG and its combination with NSS failed to cause any significant difference in the kidney function parameters in comparison with the control. A significant elevation in lipid peroxides (LPO) level, glutathione-S-transferase activity and total antioxidant capacity (TAC) and a significant reduction in superoxide dismutase activity were found in MSG group. LPO level and TAC in MSG intoxicated rats significantly normalized by NSS ingestion. NO level showed absence of significant difference among all experimental groups. MSG elicited histopathological lesions such as depleted glycogen content and fibrosis however, NSS succeeded in enhancing all these features. MSG group showed positive glutathione reductase and superoxide dismutase 2 immuno-expression whereas, MSG+NSS group showed weak immunostaining. A significant increase in the number of apoptotic cells was observed in MSG group compared to the control. On the other hand, MSG+NSS group exhibited a significant decrease in the number of apoptotic cells. NSS mitigated MSG-induced renal impairments by ameliorating oxidative stress and exerting anti-apoptotic effect.